Respiratory Tuberculosis in Those over 70 Years of Age: Specific Course of the Disease and Diagnostic Difficulties - A. S. Shprykov; D. A. Sutyaginа; M. A. Dolgovа (Туберкулез и болезни лёгких)
The objective: to study specific features of the course and diagnosis of respiratory tuberculosis in persons aged 70 years and older.Subjects and methods. Medical records of 93 patients aged 70 years and older who were hospitalized due to respiratory tuberculosis in 2000-2019 were retrospectively analyzed. Men made 60.2%, and women – 39.8%.Results. Often tuberculosis was detected late when referring for medical care (68.8%). In 59.4% of patients, tuberculosis was detected later than in 2 months after the onset of the first symptoms. 89.2% had multiple co-morbidities. Destruction was detected in 52.7% of patients, bacterial excretion – in 69.9%, and remaining post-tuberculosis changes – in 34.4%. Sputum conversion was achieved in 81.5% of patients and cavities were healed in 53.1%.